2009
DOI: 10.1128/mcb.00090-09
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation-Dependent Interactions between RUNX-1 and FLI-1 during Megakaryocyte Development

Abstract: The transcription factor RUNX-1 plays a key role in megakaryocyte differentiation and is mutated in cases of myelodysplastic syndrome and leukemia. In this study, we purified RUNX-1-containing multiprotein complexes from phorbol ester-induced L8057 murine megakaryoblastic cells and identified the ets transcription factor FLI-1 as a novel in vivo-associated factor. The interaction occurs via direct protein-protein interactions and results in synergistic transcriptional activation of the c-mpl promoter. Interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 68 publications
2
71
0
Order By: Relevance
“…Low-ploidy MK has been observed in KO of other transcription factors, such as GATA1 or FLI-1 (refs 37,38). As these two transcription factors may be associated with RUNX1 in large transcription complexes 39,40 , they may similarly act on MYH10 expression. The observation that two non-muscle myosin II isoforms are present in MK and have distinct roles opens new avenues of research; for example, the MYH9/MYH10 ratio could be used as a marker of MK differentiation and dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Low-ploidy MK has been observed in KO of other transcription factors, such as GATA1 or FLI-1 (refs 37,38). As these two transcription factors may be associated with RUNX1 in large transcription complexes 39,40 , they may similarly act on MYH10 expression. The observation that two non-muscle myosin II isoforms are present in MK and have distinct roles opens new avenues of research; for example, the MYH9/MYH10 ratio could be used as a marker of MK differentiation and dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of STAT1, a known signaling molecule responsible for megakaryocyte differentiation, was also increased upon PMA stimulation and PITHD1 did not affect PMA-induced STAT1 phosphorylation. In addition, we measured the expression of several transcription factors that played important roles in megakaryocyte differentiation [18][19][20]. We discovered that PITHD1 overexpression increased RUNX1 protein but not for GATA1, FLI1, or GABPa (Fig.…”
Section: Pithd1 Enhances Pma-induced Megakaryocyte Differentiation Inmentioning
confidence: 99%
“…18 Fli-1-mediated activation of megakaryocytic promoters is further dependent on the cooperation with Fog1 and/or Aml1. 19 We 20 and others 21,22 recently demonstrated that Eklf promotes the commitment of bipotent progenitors toward erythrocytic at the expense of megakaryocytic The online version of this article contains a data supplement.The publication costs of this article were defrayed in part by page charge payment. Therefore, and solely to indicate this fact, this article is hereby marked ''advertisement'' in accordance with 18 USC section 1734.…”
mentioning
confidence: 99%